Tropism of Pandemic 2009 H1N1 Influenza a Virus - Ramadhany, Ririn; Yasugi, Mayo; Nakamura, Shota; Daidoji, Tomo; Watanabe, Yohei; Takahashi, Kazuo; Ikuta, Kazuyoshi; Nakaya, Takaaki (Frontiers in Microbiology, 2012)
Substitutions at the receptor-binding site of the pandemic H1N1 2009 influenza A virus (H1N1pdm) hemagglutinin (HA) gene may be critical in determining whether a virus binds to human or avian receptors. Previous reports suggest that HA Gly222 and/or Arg223 allow viruses to bind preferentially to the α2,3-linked sialic acid found in avian species. We also demonstrated that serial passaging of influenza A virus in embryonated chicken eggs increased viral growth 32- to 64-fold, coincident with the increased prevalence of Gly222 or Arg223 in HA protein (Yasugi et al., 2012). In this study, we showed that the minor genotype of α2,3-linkage-tropic viruses in upper airways became dominant after passaging through chicken eggs. Viruses possessing HA containing N125D-Q223R, N125D-D187E-Q223R, K119N-D222G, and K119N-N129S-D222G, were detected in both clinical specimens and egg-passaged samples. These results might suggest that egg-adapted viruses, likely represented by α2,3-linkage-tropic virus, were also present in human upper airways as a minor population and transmitted in humans during the outbreak of H1N1pdm.